Studi Empirik BUMN Pada PT PELINDO III Surabaya Pengaruh Intellectual Capital Terhadap Inovasi Organisasi - arfah, arfah (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2021)
The era of the industrial revolution 4.0. In the last century, experts have increasingly convinced that the intellectual resources of an organization determine the competitive advantage of an organization in accelerating the effectiveness of artificial intelligence, especially in presenting the best customer service innovation products. However, there are only a few studies on the relationship between intellectual capital and innovation. Based on the importance of these issues, this study aims to examine the impact of intellectual capital on organizational innovation. Questionnaires have been distributed to 100 employees of PT. Pelindo from Indonesian State-Owned Enterprises (BUMN), and 82 usable questionnaires were returned. The regression statistical method analysis was used to test the hypothesis. The results of the research simultaneously show that intellectual capital has a positive and significant effect on organizational innovation. The next test results partially prove that human capital, organizational capital, and relational capital have a significant and positive effect on organizational innovation. This study opens several pathways for innovation program projects in future Indonesian organizations. The significance of the findings of this study shows the practical implications of the support in the next roadmap on research and development (R&D) of Human Resources and innovation of Indonesian BUMN organizations, particularly at PT. Pelindo as one of the important pillars in the success of the vision of the Indonesian government's maritime axis. Based on the high level of socio-cultural heterogeneity in Indonesia, the implications of follow-up studies are important to expand the sample of employees to a larger and more diverse range and combine other independent variables (such as demographic factors, organizational culture, organizational climate, leadership, job satisfaction or other motivational factors) which may result in different study findings and recommendations.